The duty to treat in the context of the Covid-19 pandemic - Isaila, Oana Maria (2020)
The duty to treat has been at the center of the moral and public debate surrounding the physician-patient relationship, especially in epidemics. The topic of discussion may be the physician who “fights” (the “hero physician”), the contaminated professional, the doctor who refuses to treat or the resigning physician. This may increase potential conflicts between the physicians’ individual values and those of their patients, conflicts that can have personal and social consequences. Doctors implicitly assume that treating patients may generate risks for his/her own well-being, but none should accept risks related to insufficient protective equipment or inappropriate protocols, or other external causes that unjustifiably increase them. Everybody involved in healthcare has the duty to minimize the risks imposed on the patient; otherwise not only physicians are at risk, but also patients and society, which could receive less healthcare or even develop other diseases. Keywords: Coronavirus infections. Pandemics. Risk. Beneficence.